2019
DOI: 10.1021/acscatal.9b02578
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Cu Cations in Cu-CHA Catalysts for NH3-SCR: Effects of SiO2/AlO3 Ratio and Cu-Loading Investigated by Transient Response Methods

Abstract: We develop an experimental protocol to quantify the speciation of Cu ions (ZCu II OH and Z 2 Cu II ) in Cu-CHA catalysts for the NH 3 Selective Catalytic Reduction of NOx (NH 3 -SCR). Toward this end, we performed four transient tests, namely H 2 -TPR, NO + NH 3 TPR, NO 2 adsorption + TPD, and NH 3 adsorption + TPD, over two sets of Cu-CHA research catalysts characterized by different Cu contents (0−2.1% w/w) and SiO 2 /Al 2 O 3 (SAR) ratios (10−25). Preliminary H 2 -TPR tests on the samples with the extreme S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
157
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 110 publications
(172 citation statements)
references
References 33 publications
14
157
1
Order By: Relevance
“…Recently, we proposed an experimental protocol which allows to quantify directly the number of ZCu II OH and Z 2 Cu II ions by applying simple transient response methods based on the dry Cu II reduction by NO + NH 3 and on the nitrates storage/desorption via NO 2 adsorption + TPD. [4] For several different CuÀ CHA samples, such an approach gave estimates of the two Cu species consistent with those generated by H 2 À TPR and NH 3 adsorption/desorption tests, i. e. the established and most popular techniques for the Cu speciation, which however may require complex deconvolutions of the experimental signals. [1][2][3][4][5] Although ZCu II OH and Z 2 Cu II ions are generally regarded as the active sites for the standard SCR mechanism, some literature works considered the possibility that other Cu species, like dimeric copper-oxo species or CuOx nanoclusters, could play a role in redox catalytic mechanisms over Cu-zeolites.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Recently, we proposed an experimental protocol which allows to quantify directly the number of ZCu II OH and Z 2 Cu II ions by applying simple transient response methods based on the dry Cu II reduction by NO + NH 3 and on the nitrates storage/desorption via NO 2 adsorption + TPD. [4] For several different CuÀ CHA samples, such an approach gave estimates of the two Cu species consistent with those generated by H 2 À TPR and NH 3 adsorption/desorption tests, i. e. the established and most popular techniques for the Cu speciation, which however may require complex deconvolutions of the experimental signals. [1][2][3][4][5] Although ZCu II OH and Z 2 Cu II ions are generally regarded as the active sites for the standard SCR mechanism, some literature works considered the possibility that other Cu species, like dimeric copper-oxo species or CuOx nanoclusters, could play a role in redox catalytic mechanisms over Cu-zeolites.…”
mentioning
confidence: 69%
“…[4] For several different CuÀ CHA samples, such an approach gave estimates of the two Cu species consistent with those generated by H 2 À TPR and NH 3 adsorption/desorption tests, i. e. the established and most popular techniques for the Cu speciation, which however may require complex deconvolutions of the experimental signals. [1][2][3][4][5] Although ZCu II OH and Z 2 Cu II ions are generally regarded as the active sites for the standard SCR mechanism, some literature works considered the possibility that other Cu species, like dimeric copper-oxo species or CuOx nanoclusters, could play a role in redox catalytic mechanisms over Cu-zeolites. [6][7][8][9][10] Da Costa et al [6] studied a series of CuÀ ZSM5 samples with varying Cu/Al ratios and reported evidence for the involvement of Cu II dimers with one bridging extra framework oxygen atom in the direct NO decomposition to N 2 .…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…The fractional coverages of Z 2 W, ZCu1, ZCu2 and ZB for the degreened sample were, therefore, 0.60, 0.21, 0.12 and 0.07, respectively. The stoichiometry between a certain active site and NH 3 [18,47,56] was lumped into to the reaction rate parameters, similar to the prior literature [30,44]. Figure 5 shows the NH 3 concentration at the outlet of the reactor during NH 3 adsorption, isothermal desorption and TPD along with the fractional coverages obtained using the 4-site transient kinetic model for the degreened Cu-CHA.…”
Section: Zcu2mentioning
confidence: 99%